The effect of temperature and salinity on Margalefidium polykrikoides group III VA, USA strain growth - Perez-Vega, Eduardo; Mulholland, Margaret R; Crider, Katherine E; Powell, Kimberly E; Chappell, P Dreux; Bochdansky, Alexander B (PANGAEA, 2025)
M.polykrikoides is a cosmopolitan harmful dinoflagellate that blooms in coastal waters worldwide. Despite genomic evidence that it is in Group III and so closely related to isolates from Puerto Rico, Malaysia, North America, and Central America, M. polykrikoides group III VA, isolated from the lower Chesapeake Bay, bloom at warmer temperatures and lower salinities than in coastal ecosystems occupied by its closest relatives. In contrast, M. polykrikoides blooms in other regions initiate when salinities are higher (e.g., 30) and water temperatures are cooler, leading to the question of whether there are differences in salinity and temperature preferences for different groups and strains of M. polykrikoides, or whether the realized niche of M. polykrikoides varies based on local conditions and competitive interactions . In this study, the effect of temperature and salinity on the exponential growth rate and total cell yield of an M. polykrikoides VA culture isolate were examined. A clonal culture of M. polykrikoides (MP-LRCB-082419) was established by isolating a cell from the Lafayette River, a sub-tributary of the lower Chesapeake Bay, on August 24, 2019. Lafayette River water of 20 salinity was filtered through Thermo ScientificTM NalgeneTM Rapid-FlowTM sterile, 1,000 mL disposable filter units containing a 90 mm diameter and 0.1 µm pore size PES membrane. Filtered river water was augmented with L1 medium (Guillard & Hargraves, 1993) nutrient concentrations (excluding silicate) that was then used as the culture medium. The M. polykrikoides cell was isolated in Dr. Margaret Mulholland's lab via serial transfer into fresh medium using a 100-1000 µL Eppendorf® Research® pipette, Costar® 12-well clear TC-treated sterile well plates, and an OLYMPUS CKX41 inverted microscope. Then, the cell was inoculated into VWR® tissue culture flasks (25mL, non-treated, plug seal cap, and sterilized) containing L1 medium and incubated at 28 ̊ C, under 140µmol photons m-2 s-1 lights on a 14 h:10h light:dark cycle. M. polykrikoides cultures were acclimated to multiple temperature (16, 18, 20, 24, 28, 30, 32, and 34 ̊ C) and salinity (10, 15, 20, 25, and 30) treatments by stepwise transfer for 7 to 38 days (Yamaguchi & Honjo, 1989). Light was maintained under constant conditions at 140 µmol photons m-2 s-1 supplied over a 14h:10h light:dark cycle. Cultures in exponential growth phase were used to inoculate cells into tissue culture flasks(25mL) containing L1 medium and exposed to the different temperature and salinity treatments in triplicate. The initial cell concentration for all the experiments was 1,200 cells mL-1. The experiments duration was 7, 14, 28, or 35 days. Samples (3mL each) were collected during seven timepoints every 1, 2, 4, or 5 days and alkaline Lugol's solution was added to preserve M. polykrikoides cells. M. polykrikoides cells were quantified from these preserved samples under bright field using an OLYMPUS BX51 microscope and a Palmer-Maloney counting chamber. The growth rate was calculated by finding the best fit to the classic logistic growth model with the MATLAB curve fitting toolbox: N_t=K/(1+(e^(-r(-b+t) ))) , where "N_t" is the cell concentration at time "t", K is the total cell yield, "r" is the exponential growth rate coefficient, and "b" the time of inflection of the curve (Garnier & Quetelet, 1838). However, when the classic logistic growth model did not fit the data because the asymptote was reached within one or two time intervals or was never reached, the following model was used to calculate the growth rate: N_t = N_0 e^rt , where "N_t " is the cell concentration at time "t", "N_0" was the initial cell concentration, and "r" is the growth rate coefficient (Andersen, 2005).
Keywords: culture growth experiment; Dinoflagellate; growth rate; harmful algae; Laboratory experiment; Margalefidinium polykrikoides group III; Salinity; Temperature; total cell yield